Pengaruh Media E-Learning Berbasis LMS Moodle dan Motivasi Belajar terhadap Hasil Belajar Mahasiswa di Masa Pandemi Covid-19 - Fakhri, M. Miftach; Fadhilatunisa, Della; Rosidah, Rosidah; Fajar B, Muhammad; Satnur, Muh. Alham; Fajrin, Farid (Chemistry Education Review (CER), 2022)
Online learning in E-learning Media in Covid-19 conditions involving lecturers as educators and students as educators has an important role in improving student learning outcomes.  The purpose of this study was to find out the influence of E-learning based on LMS Moodle and Motivation to Learn partially and simultaneously on student learning outcomes. This type of research is a mix method that integrates quantitative and qualitative research with sequential explanatory forms. The data collection techniques used are questionnaires or questionnaires and interviews. The instruments used are questionnaire sheets and interviews that are used to collect the data needed. The sample from this study was 75 accounting students. The data analysis used is inferential analysis with Classical Assumption Test (Normality Test and Linearity Test) and Multiple Regression Analysis with partial t test and simultaneous F test. The results showed that there was an influence of LMS Moodle-based E-learning Media, Partial and simultaneous Learning Motivation on student learning outcomes which was indicated by a significant value smaller than 0.05 and the large influence of both variables on dependent variables of 60.6%.